2022
DOI: 10.1002/ijc.34249
|View full text |Cite
|
Sign up to set email alerts
|

Targeting YAP1/TAZ in nonsmall‐cell lung carcinoma: From molecular mechanisms to precision medicine

Abstract: Accumulating evidence has underscored the importance of the Hippo-YAP1 signaling in lung tissue homeostasis, whereas its deregulation induces tumorigenesis. YAP1 and its paralog TAZ are the key downstream effectors tightly controlled by the Hippo pathway. YAP1/TAZ exerts oncogenic activities by transcriptional regulation via physical interaction with TEAD transcription factors. In solid tumors, Hippo-YAP1 crosstalks with other signaling pathways such as Wnt/β-catenin, receptor tyrosine kinase cascade, Notch an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 134 publications
0
7
0
Order By: Relevance
“…YAP1, a transcriptional regulator, is widely activated in various human malignancies, including GBC [ 34 , 37 , 38 ]. Studies have shown that YAP/TAZ plays an essential role in cancer initiation or growth of most solid tumors [ 39 , 40 ]. YAP1 interacts with the PPxY motif via its WW domains, leading to post-transcriptional modifications (PTMs) at different sites, contributing to its stability and spatial regulation [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…YAP1, a transcriptional regulator, is widely activated in various human malignancies, including GBC [ 34 , 37 , 38 ]. Studies have shown that YAP/TAZ plays an essential role in cancer initiation or growth of most solid tumors [ 39 , 40 ]. YAP1 interacts with the PPxY motif via its WW domains, leading to post-transcriptional modifications (PTMs) at different sites, contributing to its stability and spatial regulation [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated YAP activity has been strongly associated with the development of cancer 38,41 . Elevated YAP expression has been observed in oral, breast, lung, and liver cancers 42–45 . In HNSCC, frequent deletion or truncation of FAT1 disperses Hippo components and leads to aberrant activation of YAP via suppressing its ubiquitination 46 .…”
Section: Discussionmentioning
confidence: 99%
“… 38 , 41 Elevated YAP expression has been observed in oral, breast, lung, and liver cancers. 42 , 43 , 44 , 45 In HNSCC, frequent deletion or truncation of FAT1 disperses Hippo components and leads to aberrant activation of YAP via suppressing its ubiquitination. 46 As gene alterations of FAT1 is frequently occurred in HNSCC, 47 FAT1 gene alterations may be involved in the prevalent YAP activation in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…The migration of cancer cells is a main cause of increased cancer deaths [35,36]. The in vitro wound scratch tests were utilised to examine the migration and invasion of L929 cells and A549 cells against chaetocin.…”
Section: Assessment Of Migration and Invasion Of L929 And A549 Cellsmentioning
confidence: 99%